Your freedom and mine Abdullah Öcalan and the Kurdish question in Erdogan's Turkey - Miley, Thomas Jeffrey; Venturini, Federico (Black Rose Books, 2018)
"Your Freedom and Mine tells the story of the Imrali Delegations' attempts to meet with Abdullah Öcalan and provides context for an understanding of the conflict between Turkey and the Kurdish people. The book opens with a historical view of the Kurdish Question, leading up to the optimistic opening-and eventual bitter failure-of the peace process in Turkey. It includes official documents and reports from the Imrali Delegations in Istanbul and Diyarbakir/Amed, which involved in-depth interviews with Kurdish and Turkish politicians, media, and civil society regarding the degenerating political and human rights situation. The final section is a collection of testimonials from delegation participants. Your Freedom and Mine offers crucial insight into the dramatic history and current reality of the Kurdish struggle for recognition and peace in Turkey."--
Keywords: Öcalan, Abdullah -- 1949-; Geschichte 2000-; Politik; Kurden; Türkei; Öcalan, Abdullah; Kurds / Turkey / Politics and government / 21st century; Turkey / Politics and government / 21st century; Kurds / Politics and government; Politics and government; Turkey; 2000-2099